Entrepreneurship and the Post-COVID-19 Recovery in Emerging Economies. (December 2021) - Meyer, Klaus E.; Prashantham, Shameen; Xu, Shiqi
ABSTRACT: Entrepreneurs play a focal role in a society's economic recovery from major disruptions such as the COVID-19 pandemic. We argue that entrepreneurs' ability to identify and act on entrepreneurial opportunities during the crisis reflects their resilience, and their innovations facilitate new patterns of work, learning, and leisure activities in post-COVID-19 societies. However, how, how quickly they act, and how influential their actions are depends on their context in terms of institutions, resource access, and market volatility. In China, some entrepreneurs have shown great resilience by utilizing network relationships and digital technology, not only to overcome short-term disruptions in 2020 but to shape the evolving 'new normal' where behaviors and capabilities have changed as a consequence of the experience of the pandemic. We discuss drivers of such resilient entrepreneurship during the COVID-19 pandemic in China and call for further research on the interplay between external disruptions, different types of entrepreneurship, and the consequences for resilience in emerging economies. 摘要: 企业家们在社会遭遇如新冠疫情等重大冲击后的经济复苏中扮演着举足轻重的角色。我们认为企业家们在困境中所表现出来的识别创业机会并采取行动的能力反应了他们企业的韧性。这些企业家们的创业创新在后疫情时代为社会带来了新的工作、学习以及娱乐模式。然而，企业家们如何行动，以及他们的行动有多大影响力，取决于他们在制度、资源获取和市场结构方面的背景及条件。 在中国，一些企业家利用网络关系和推进数字技术两方面表现出卓越的复原力，这些方式不仅在2020年帮助企业克服了短期困境，而且创造了由于疫情期间行为和能力的变化所带来的"新常态"。本文聚焦讨论在中国后疫情时代中这种创业企业韧性的驱动因素，并呼吁学者们进一步研究三类因素：外界干扰、创业类型、企业韧性结果，以及它们之间在新兴市场中的相互作用。